PHONOLOGY AND LANGUAGE LEARNING : PRACTICAL TIPS - Br Surbakti, Reinasya; Dini Aghnianty Harahap; M. Ilham Khanis; Syahrul Effendi Lubis (PT Rahis Cendekia Indonesia, 2025)
This article explores the essential role of phonology in second language acquisition and highlights effective strategies for integrating phonological awareness into language learning processes. Phonology, which deals with the sound systems and patterns of language, is foundational for learners to develop accurate pronunciation, enhance listening comprehension, and communicate effectively in a new language. Drawing on a combination of recent research findings and practical classroom experiences, the article presents a variety of actionable techniques aimed at both educators and learners. These include methods for improving pronunciation accuracy, exercises to develop auditory discrimination skills, and activities designed to strengthen phonological memory. A strong emphasis is placed on adopting a learner-centered approach, where instruction is tailored to individual needs and learning styles, as well as the importance of contextualized practice that situates phonological skills within meaningful communication settings. By bridging the gap between theoretical insights and classroom application, the article provides accessible and effective tools that can be readily incorporated into language teaching curricula. Ultimately, the goal is to enhance overall language proficiency by fostering phonological competence, thereby supporting learners in overcoming common challenges related to sound perception and production in second language learning.